Watershed cerebral infarction secondary to idiopathic orbital inflammatory disease - Ramírez-Quiñones, Jorge A. (2018)
Watershed cerebral infarctions are those located in regions between two adjacent vascular territories and Idiopathic orbital inflammatory disease is a nonspecific inflammatory process of the orbit. We report the case of a 60-year-old man who presented suddenly in the right eye: exophthalmos, ptosis, reduced visual acuity and paresis of the extraocular muscles innervated by the III, IV and VI cranial nerves. Imaging studies showed a right retro-ocular mass with invasion of the ipsilateral cavernous and sphenoid sinus. During hospitalization, suddenly he presented a watershed infarction with narrowing of the right internal carotid artery in its intracavernous portion. Surgical excision of the lesion was performed and pathology showed a characteristic infiltration of idiopathic orbital inflammatory disease. Our case shows idiopathic orbital inflammatory disease as an uncommon cause of watershed cerebral infarction.